Study on the comparison between Bosentan and Macitentan in the treatment of persistent pulmonary hypertension of the newborns, simultaneously on sildenafil: A randomized double-blinded non-inferiority parallel clinical trial - Mandana Kashaki; Arash Mohazzab; Mohammad Radgoudarzi; Arash Bordbar; Sama Dabbagh (Pediatrics and Neonatology)
Background: Persistent Pulmonary Hypertension of the newborn (PPHN) is characterized by sustained elevated Pulmonary Artery Pressure (PAP). Drug resistance and the adverse effects of current therapeutic agents warrant investigation of other targeted therapies. Bosentan has shown benefits in affected neonates. However, trials reported the association with unwanted effects. Thus, in this study, we assess another agent in the same family, Macitentan. However, its efficacy in the treatment of PPHN is not yet reported. Hence, this study evaluated the effect of Macitentan compared to Bosentan in terms of efficacy and safety in the treatment of PPHN. Methods: This randomized, double-blinded non-inferiority clinical trial was conducted in Shahid Akbar Abadi hospital, Tehran, Iran. Sixty clinically stable neonates with signs suggestive of PPHN were randomly allocated into two groups (n = 30 in each group) and they received either Bosentan 1 mg/kg/dose BD (twice daily) or Macitentan 1 mg/kg/dose BD simultaneously with sildenafil. The echocardiographic and laboratory indices of efficacy and safety were compared between groups. SPAP (systolic pulmonary artery pressure) was used to assess the non-inferiority of the Macitentan compared to the Bosentan in their respective doses used in the study. Results: Participants’ mean (SD) age was 3.53 (1.21) days, and 55% were female. No mortality case occurred. SPAP was reduced in both Bosentan and Macitenan groups with the mean difference in SPAP of 9 (95% CI: 7.34–10.65) in Bosentan and SPAP mean difference of 14 (95% CI: 12.12–15.86) in Macitentan group. Categorical comparison of primary outcome improvement showed that Macitentan was superior to Bosentan with a 10% non-inferiority margin. Similar results were obtained in other echocardiographic indices. Also, no significant alterations were observed in laboratory safety parameters. Conclusion: Macitentan 1 mg/kg/dose BD (twice daily) is non-inferior to Bosentan 1 mg/kg/dose BD in improving echo outcomes of PPHN and it was even more effective in improving some of these. Also, it is non-inferior to Bosentan in terms of safety. Trial registry number: (IRCT20160120026115N9).